2018
DOI: 10.9734/jeai/2018/43891
|View full text |Cite
|
Sign up to set email alerts
|

Individual and Competitive Adsorption of Copper, Zinc and Lead in Soils with Contrasting Texture

Abstract: Waste is often disposed of in the soil, leading to contamination not only by a metal, but by two or more elements. The adsorption studies are a way of evaluating the behaviour of the different metals when in contact with the soils. This study aimed to evaluate the effect of adsorption of Cu, Zn and Pb, in an individual and competitive system, in soils with contrasting texture. To achieve the goals,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Soils with high organic matter, high CEC, and high pH exhibited strong adsorption for Zn, but with no exception for Cd, Cu, Ni, and Pb [41]. However, competitive adsorption behaviors between different heavy metals would produce great influence [42,43]. When Cu was present, Zn was weakly bound to soil surfaces and was released in high amounts during desorption [44].…”
Section: Risk Assessment Of Groundwater By Heavy Metals In Sludgementioning
confidence: 99%
“…Soils with high organic matter, high CEC, and high pH exhibited strong adsorption for Zn, but with no exception for Cd, Cu, Ni, and Pb [41]. However, competitive adsorption behaviors between different heavy metals would produce great influence [42,43]. When Cu was present, Zn was weakly bound to soil surfaces and was released in high amounts during desorption [44].…”
Section: Risk Assessment Of Groundwater By Heavy Metals In Sludgementioning
confidence: 99%
“…In sludge application, the high concentration of zinc (heavy metal) in the sludge (514 mg.kg -1 ) used in the present study, and reported by Amaral et al (2018), was responsible for the impacts in this category. According to Kummer et al (2018), zinc has a low potential for adsorption in soils and, thus, is easily leached into rivers and groundwater.…”
Section: Environmental Assessment Of the Stp With Sludge Destined For Agriculture Usementioning
confidence: 99%